2022
DOI: 10.1155/2022/2253436
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Inhibition of Accumulation and Function of Myeloid-Derived Suppressor Cells by Artemisinin via PI3K/AKT, mTOR, and MAPK Pathways Enhances Anti-PD-L1 Immunotherapy in Melanoma and Liver Tumors

Abstract: Despite the remarkable success and efficacy of immune checkpoint blockade (ICB) therapy such as anti-PD-L1 antibody in treating cancers, myeloid-derived suppressor cells (MDSCs) that lead to the formation of the protumor immunosuppressive microenvironment are one of the major contributors to ICB resistance. Therefore, inhibition of MDSC accumulation and function is critical for further enhancing the therapeutic efficacy of anti-PD-L1 antibody in a majority of cancer patients. Artemisinin (ART), the most effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Ginsenoside Rk1 can also inhibit the proliferation of lung cancer cells by suppressing the expression of PD-L1 . Additionally, artemisinin has been reported to augment the efficacy of PD-L1 immunotherapy for liver cancer through the MAPK signaling pathway . Similarly, we demonstrated that PD-L1 expression was inhibited after the addition of GGO, highlighting the potential of GGO as an immune suppressor and providing direction for future research.…”
Section: Discussionsupporting
confidence: 60%
“…Ginsenoside Rk1 can also inhibit the proliferation of lung cancer cells by suppressing the expression of PD-L1 . Additionally, artemisinin has been reported to augment the efficacy of PD-L1 immunotherapy for liver cancer through the MAPK signaling pathway . Similarly, we demonstrated that PD-L1 expression was inhibited after the addition of GGO, highlighting the potential of GGO as an immune suppressor and providing direction for future research.…”
Section: Discussionsupporting
confidence: 60%
“…Epigenetic modifiers such as HDAC inhibitors have thus been identified to promote sensitization of tumor cells to PD-1/PD-L1 immune checkpoint inhibitors via reversal of MDSC’s immunosuppressive effect on the cancer milieu, demonstrating synergistic effects with immunotherapeutic options in solid tumors ( 212 ). We observe further agents such as artemisinin used in MDSC suppression, which improved the efficacy of anti-PD-L1 blockade therapy in mice with T cell lymphoma ( 213 ). The presence of a deficiency in the MDSC-polarizing TIPE2 gene additionally informed of MDSC activity and thus delayed tumor progression in mice ( 214 ).…”
Section: Emerging Biomarker Landscape In Ptcl and Nktclmentioning
confidence: 94%
“…Ginsenoside-Rg3 inhibited cell proliferation and invasion of SMMC-7721 cells through PI3K/AKT pathway, which effectively decreased the levels of phosphorylated (p)-AKT, p-PI3K, MMP2, MMP9 and long non-coding RNA HOX antisense intergenic (lncRNA HOTAIR) (40). Recently, Zhang et al showed that artemisinin enhanced the effect of anti-programmed cell death-ligand 1 (anti-PD-L1) immunotherapy by blocking the accumulation and function of myeloid-derived suppressor cells (MDSCs) via regulating PI3K/ AKT/mTOR and MAPK signaling pathways and polarizing M2-like pro-tumor phenotype to M1-like anti-tumor phenotype (41). Dihydroartemisinine inhibits proliferation and induces apoptosis of HepG2 cells through regulating Bcl-2/Bax/caspase-3 apoptosis signal pathway (42).…”
Section: Terpenoidsmentioning
confidence: 99%
“…Recently, Zhang et al. showed that artemisinin enhanced the effect of anti-programmed cell death-ligand 1 (anti-PD-L1) immunotherapy by blocking the accumulation and function of myeloid-derived suppressor cells (MDSCs) via regulating PI3K/AKT/mTOR and MAPK signaling pathways and polarizing M2-like pro-tumor phenotype to M1-like anti-tumor phenotype ( 41 ). Dihydroartemisinine inhibits proliferation and induces apoptosis of HepG2 cells through regulating Bcl-2/Bax/caspase-3 apoptosis signal pathway ( 42 ).…”
Section: Plant-derived Natural Products In the Treatment Of Liver Cancermentioning
confidence: 99%